Implementation of Correction to Answer Questions Essay Using Vector Space Model - Ipin Sugiyarto; Umi Faddillah; Arina Selawati (Universitas Islam Sultan Agung, 2018)
Correction answers to the essay still use manual way to judge based personal weight determined by each teacher. Correction value calculation result of the answers to the essay can use the quick way by computational methods. Used computational methods based text mining to test the system using the information retriveral vector space model. The result of the test method vector space model obtained by election the second-highest rank of valid answer content to answer valid student and teachers. Answer approach contained in rank-2 closest rank-1 with the result of the closest distance between the has a similarity value for student 0.45 and 0.10 teacher similarity value.Keywords: correction, vector space model, rank, similarity